Personalized antiplatelet therapy guided by clopidogrel pharmacogenomics in acute ischemic stroke and transient ischemic attack: A prospective, randomized controlled trial - Zhang, Xiaoguang; Jiang, Shanshan; Xue, Jie; Ding, Ying; Gu, Jingyu; Hu, Liang; Xu, Xushen; Li, Zhizhang; Kong, Yuming; Li, Youmei; Zhu, Xiaoqiong; Yue, Yunhua (Frontiers in Pharmacology, 2023)
Background: Clopidogrel is frequently used in patients with ischemic stroke or transient ischemic attack (TIA), but its efficacy is hampered by inter-individual variability, due to genetic differences associated with clopidogrel metabolism. We conducted this randomized controlled trial to validate whether the personalized antiplatelet therapy based on clopidogrel pharmacogenomics and clinical characteristics leads to better clinical outcomes compared with standard treatment. Methods: Patients were randomly into the standard group or pharmacogenetic group, in which the pharmacogenetic group required the detection of the genotyping of CYP2C19*2, CYP2C19*3, CYP2C19*17. Patients were followed for 90 days for the primary efficacy endpoint of new stroke events, secondary efficacy endpoint of individual or composite outcomes of the new clinical vascular events and the incidence of disability. The primary safety outcome was major bleeding. Results: A total of 650 patients underwent randomization, among which 325 in the pharmacogenomics group while 325 in the standard group. Our study found after 90-day follow-up, the risk of stroke and composite vascular events in the pharmacogenomic group was lower than that in the standard group. The incidence of disability significantly decreased in the pharmacogenomic group. In addition, no statistically significant differences were observed in bleeding events between the two groups. Conclusion: The present study demonstrates that personalized antiplatelet therapy guided by clopidogrel pharmacogenomics and clinical characteristics can significantly improve the net clinical benefit of ischemic stroke or TIA patients during the 90-day treatment period without increasing bleeding risk.